Implementasi Master-slave pada Embedded system menggunakan komunikasi RS485 - Wajiansyah, Agusma; Supriadi, Supriadi (ELKHA : Jurnal Teknik Elektro, 2020)
The use of multiprocessor methods in robotics systems has a significant impact on overall robot performance. The Master-slave method is a model of a multiprocessor system where there are several processors that communicate with each other to carry out the robot's overall function. RS-485 can be used as a communication model in the master-slave method. RS-485 is a development of RS-232 which has the ability to communicate with several nodes. In this research, an experiment will be conducted to implement RS-485 to support the master-slave processor communication. Stages of research began with making system design, which includes the design of embedded hardware systems, the design of data communication protocols on RS-485 networks, software design, followed by implementation and testing. The test is carried out to measure the time response of the device to three data transmission models, namely broadcast, addressing slaves without responding and addressing slaves with responses. The test results carried out on three slaves with a communication speed of 9600 bps. Measured response time on broadcast data transmission is 8ms, and address slave without response is 7ms. Whereas delivery by addressing slaves with responses, shows that the measurement method cannot be applied.